Cloning enzymes of the taxol pathway and their expression in transgenic tomato - Alzahrani, Fatima (2016)
Paclitaxel (Taxol) was first isolated from the bark of the pacific yew tree as an important anticancer compound. Its efficacy and unique mode of action has seen demand increase, but full chemical synthesis is not economically viable and this has led to a search for alternative production sources. Current supply is met by semi- synthesis from its natural precursor, 10-deacetylbaccatin III (found in yew tree needles) or from yew cell suspension cultures. However, engineering of the key biosynthetic genes into heterologous hosts could provide an alternative for paclitaxel production. This study aimed to utilise the geranylgeranyl diphosphate precursor pool present in fruit of the yellow flesh (r) tomato mutant for the production of novel taxanes. A synthetic polycistronic construct was designed and created to contain the first four Taxol biosynthetic pathway genes, which were codon-optimised for recombinant protein expression in tomato plants. The first genes in the Taxol biosynthesis pathway, namely taxadiene synthase (TXS), taxadien-5α-hydroxylase (T5OH), taxadien-5α-acetyltransferase (T5AT), and taxoid 10β-hydroxylase (T10BOH) were successfully introduced into tomato plants using an optimised Agrobacterium-mediated transformation protocol. Plants expressing the TXS and T5OH transgenes were analysed; however, GS-MS analysis failed to detect the expected compounds taxadiene and taxadiene-5α-ol. Plants harbouring TXS, T5OH, and T5AT were successfully generated, and plants containing T10BOH were also generated; however, the production of downstream taxanes or novel taxanes was not investigated owing to time constraints. The localisation of T5OH, T5AT, and T10BOH was investigated by tagging putative leader sequences to green fluorescent protein (GFP). Confocal microscopy was used to detect GFP in Arabidopsis thaliana root cells. All three Taxol biosynthetic proteins were found to be localised to the endoplasmic reticulum membrane.